Determining Gate Count Reliability in a Library Setting - Jeffrey Phillips (Evidence Based Library and Information Practice, 2016)
Objective – Patron counts are a common form of measurement for library assessment. To develop accurate library statistics, it is necessary to determine any differences between various counting devices. A yearlong comparison between card reader turnstiles and laser gate counters in a university library sought to offer a standard percentage of variance and provide suggestions to increase the precision of counts.